KAJIAN UNJUK KERJA MODEL CCHE-2D DALAM PEMODELAN WADUK IR. H. DJUANDA - , FACHRI JAHRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Problem which often encountered in the application of numerical models in fiield case is the availability of data. Although the numerical model has high accuracy in laboratory case, the accuracy can be decreased if data required as input inadiquate. This study aims to test the performance of CCHE-2D Model when applied to field case which has many limitations of data availabiility. Test is conducted through sensitivity analysis of model to mesh geometry, turbulent viscosity coefficient, time step number, and suspended load adaptation factor. This study take place on Ir. H. Djuanda Reservoir. Verification of simulation results faced difficulties due to lack of data of velocity, sediment, nor bathymetry.The result shows that stability of model is affected by mesh geometry, apllied turbulent viscosity coefficient, suspended load adaptation factor.